Reminiscing In Tempo : Ubangulo - Tutani, Zodwa (Rhodes University, Faculty of Humanities, Department of Fine Art)
My thesis is a collection of poems that focuses on black mothering and motherhood, within the context of the Eastern Cape's violent history, its oppressive patriarchal cultural traditions and religious structures. Drawing from my own experiences, my poems explore what Toni Morrison calls the historical 'wounds' of black women which are transferred to their daughters within everyday spaces like the kitchen and the lounge, through objects like tea cups, chair backs and the various foods that every black girl needs to be able to prepare in order to be 'marriagable', and how these continue to hurt and emotionally disfigure us. I also draw influence from Saidiya Hartman, Christina Sharpe and Tina Campt on black lives and the effects of slavery within their daily existences. And I am inspired by the intimacy and care with which Tadeusz Rosewicz writes about his relationship with his mother in Mother Departs and Sandra Cisneros' use of interconnected vignettes to engage childhood, culture and community within marginalized space. Stylistically I am influenced by the structural innovations in Fred Moten's The Little Edges and the dreamy landscape in the poetry of Federico Garcia Lorca. My collection includes prose and lyrical poetry, combining more formal sound and rhythmic structures with free verse, to bring to life motherhood and the narratives we carry from childhood into our adult lives.
Keywords: Creative writing (Higher education) -- South Africa; South African poetry (English) -- 21st century; South African poetry (English) -- History and criticism; Diaries -- Authorship